The effect of hydro-alcoholic extract of Kelussia odoratissma Mozaffarian (KOM) seed on histopathology & joints diameter in experimental model of Incomplete Freund,s adjuvant induced arthritis in rat - M Hoseyni Largani (Babol University of Medical Sciences, 2019)
BACKGROUND AND OBJECTIVE: Arthritis is one of the inflammatory diseases that can cause debilitating problems. Existing drugs have numerous side effects that limit their use. KOM has anti-inflammatory properties due to its flavonoid compounds. Therefore, this study was performed to investigate the anti-inflammatory effects of hydroalcoholic extract of KOM in an experimental model of arthritis. METHODS: In this experimental study, 46 male Wistar rats were randomly divided into 7 groups: healthy and patient control groups, normal saline recipient , hydrocortisone recipient and 3 groups treated with hydroalcoholic extract at doses of 300, 500 and 700 mg/kg. First, KOM was extracted then arthritis induced by injection of 0.1 cc of Incomplete Freund's adjuvant, and from 15th day KOM extract was injected intraperitoneally. On the last day (31st), their ankle joint was prepared for histological examination and the groups were compared. FINDINGS: The results showed that doses of 300, 500 and 700 mg/kg of hydroalcoholic extract did not significantly reduce joint diameter. Histologic studies of positive control group showed subcutaneous inflammation, destruction and fibrosis of cartilage and panus formation which subcutaneous inflammation was reduced in the low and high doses of the extract (p<0.05). CONCLUSION: The results of this study showed that hydroalcoholic extract of KOM reduced subcutaneous inflammation but had no significant effect on joint diameter and other histopathologic and immunological changes in IFA induced arthritis.